Pengaruh Kualitas Layanan dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan Program J3K (Jaga Kesehatan, Kebersihan dan Keamanan) Go-Ride Di Masa Pandemi: Survei Kepada Pengikut Sosial Media Instagram Gojek - Sumantri, Daffa Ramadhan; Musadad, Anwar (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to test and analyze the effect of service quality and customer satisfaction on customer loyalty in the go-ride j3k (maintain health, cleanliness, and safety) program during a pandemic. Researchers used quantitative methods with descriptive and verification approaches. The sample in this study were 386 respondents from Gojek Instagram account followers who were calculated using the Isaac and Michael formula with the Non-Probability Sampling technique, the Purposive Sampling sample method in the Gojek Instagram population. So it can be concluded that service quality has a greater contribution to customer satisfaction with a value of 0.596, and customer satisfaction has a lower contribution to customer satisfaction with an influence value of 0.045. The simultaneous effect of service quality and customer satisfaction on customer loyalty is 64.3% and the remaining 35.7% is another influence not examined in this study. Keywords : service quality, customer satisfaction, customer loyalty.